Mekong river basin and climate change: threats to Cambodia? - Haliza Abdul, Rahman (Pusat Pengajian Sains Perubatan, 2010)
Mekong River runs through China, Myanmar, Lao PDR, Thailand, Cambodia and Vietnam. Mekong's potential has been traditionally utilized both as a source of water and of susteilance, but nowadays it has become increasingly important for economic growth of countries it irrigates. In recent years, though, demands for industrialization and growth have put new pressures on the Mekong and its habitats. Most of the new development is slated to happen within China's border, which will effect the entire river system downstream including Thnle Sap Lake in Cambodia. The Thnle Sap Lake and its floodplains provide the source of livelihood and food for millions of Cambodians. Existence of dams, combined with other detrimental human interference like deforestation and pollution, causes the Mekong water level to drop, making flooding less viable. Aside from harming fisheries, the dams are putting millions out of work who make and sell products from the river, including jobs like repairing boats and making fishing gear. This will be particularly harmful to Cambodia, where so many people depend on fish and fisheries for food and employment.